The OECD Education and Social Progress Project (ESP), an international comparative study of the role of non-cognitive skills on social progress into adulthood - Daraganova, Galina; Edwards, Ben (My University, 2014)
The ESP project aims to identify learning contexts associated with the development of cognitive and non-cognitive skills and the role of skills in the development health, income and employment, crime and volunteering. Non-cognitive skills are important for two reasons: (1) they have been found to have as powerful influences on adult incomes as IQ; and (2) are more malleable than cognitive skills in middle childhood and adolescence and therefore there are more amenable to intervention. In this paper we focus on the results for Australia from analyses of data from children in the Longitudinal Study of Australian Children (LSAC) aged 4-5 to 12-13 years and from the Australian Temperament Project aged 7 to 23 years. There are a number of unique features of the paper. (1) We apply non-parametric dynamic latent variable models specifically developed for this project. (2) Rather than examine non-cognitive skills in aggregate - a limitation of the literature to date - we focus on three measures of temperament that are measured in the same manner in both studies - persistence, reactivity and sociability. (3) We examine depression and obesity in both studies. (4) We use unique features of the studies, for LSAC we use the rich data on family and learning contexts to understand how temperament and cognitive skills are influenced, while for the ATP we can examine university completion. In combination, the paper sheds new light on how families and learning contexts shape skill development and outcomes into emerging adulthood.
Keywords: Children -- Outcomes; Child Development -- Cognitive; Child Development -- Behaviour; Childhood and child development; Child Development; Children; Cognitive; Behaviour; Outcomes; Childhood and child development